Growth Performance of Hypophthalmichthys molitrix and Barbodes gonionotus Fingerlings by Feeding Microalgae Cultured on Fertilizer Factory Effluent (Bangladesh Journal of Scientific and Industrial Research, 2011)
Growth performance of Hypophthalmichthys molitrix (Silver carp) and Barbodes gonionotus (Sar puti) fingerlings were studied separately in aquaria by feeding cultured microalgae (Chlorella ellipsoidea, Scenedesmus obliquus and Spirulina platensis) in different combinations for a period of 21 days. Fertilizer factory effluent was used to grow these microalgae. Significantly (p